Efficacy of Biphasic Calcium Phosphate Ceramic With a Needle-Shaped Surface Topography Versus Autograft in Instrumented Posterolateral Spinal Fusion - Stempels, Hilde W; Lehr, A Mechteld; Delawi, Diyar; Hoebink, Eric A; Wiljouw, Inge A A A; Kempen, Diederik H R; van Susante, Job L C; Kruyt, Moyo C (Spine (Philadelphia, Pa. 1976), 2024)
A multicenter randomized controlled noninferiority trial with intrapatient comparisons. The aim of this study was to determine noninferiority of a slowly resorbable biphasic calcium phosphate with submicron microporosity (BCP<μm, MagnetOs Granules) as an alternative for autograft in instrumented posterolateral fusion (PLF). Successful spinal fusion with a solid bone bridge between the vertebrae is traditionally achieved by grafting with autologous iliac bone. However, the disadvantages of autografts and unsatisfactory fusion rates have prompted the exploration of alternatives, including ceramics. Nevertheless, clinical evidence for the standalone use of these materials is limited. Adults indicated for instrumented PLF (1 to 6 levels) were enrolled at 5 participating centers. After bilateral instrumentation and fusion-bed preparation, the randomized allocation side (left or right) was disclosed. Per segment 10 cc of BCP<μm granules (1 to 2 mm) were placed in the posterolateral gutter on one side and 10 cc autograft on the contralateral side. Fusion was systematically scored on 1-year follow-up CT scans. The study was powered to detect >15% inferiority with binomial paired comparisons of the fusion performance score per treatment side. Of the 100 patients (57 ± 12.9 y, 62% female), 91 subjects and 128 segments were analyzed. The overall posterolateral fusion rate per segment (left and/or right) was 83%. For the BCP<μm side only the fusion rate was 79% versus 47% for the autograft side (difference of 32 percentage points, 95% CI, 23-41). Analysis of the primary outcome confirmed the noninferiority of BCP<μm with an absolute difference in paired proportions of 39.6% (95% CI, 26.8-51.2; p < 0.001). This clinical trial demonstrates noninferiority and indicates superiority of MagnetOs Granules as a standalone ceramic when compared to autograft for posterolateral spinal fusion. These results challange the belief that autologous bone is the most optimal graft material.